2016
DOI: 10.1590/s1806-37562015000000166
|View full text |Cite
|
Sign up to set email alerts
|

Asthma treatment in children and adolescents in an urban area in southern Brazil: popular myths and features

Abstract: Objective: To describe the frequency of popular myths about and features of asthma treatment in children and adolescents in an urban area in southern Brazil. Methods: The parents or legal guardians of public school students (8-16 years of age) completed a specific questionnaire regarding their understanding of asthma, asthma control, and treatment characteristics. The sample included parents or legal guardians of students with asthma (n = 127) and healthy controls (n = 124). Results: The study involved 251 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
(16 reference statements)
0
7
0
3
Order By: Relevance
“…Of the parents of asthmatic children, 29% affirmed the pressurized inhaler would cause harm to the heart, while 21% of parents of non-asthmatic children said the same (p=0.009). ( 25 ) The influence of popular health myths, particularly those related to childhood asthma, is another important aspect in the management of the disease that should be better studied.…”
Section: Discussionmentioning
confidence: 99%
“…Of the parents of asthmatic children, 29% affirmed the pressurized inhaler would cause harm to the heart, while 21% of parents of non-asthmatic children said the same (p=0.009). ( 25 ) The influence of popular health myths, particularly those related to childhood asthma, is another important aspect in the management of the disease that should be better studied.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Studies have demonstrated that only 50% of patients achieve symptom control through treatment adherence as instructed by a health care team. (3) Inhaled medication use, with correct inhaler technique, reevaluation visits by a multidisciplinary team, and changes in lifestyle habits are strategic measures in the treatment of asthma in childhood. (4) Therefore, a cross-sectional study was designed with the objective of assessing the health literacy and asthma knowledge levels of guardians of children and adolescents (1-17 years old) diagnosed with the disease and registered in the Rede Bem-Estar (Wellbeing Network) in the city of Vitória, Brazil.…”
Section: To the Editormentioning
confidence: 99%
“… 2 Studies have demonstrated that only 50% of patients achieve symptom control through treatment adherence as instructed by a health care team. 3 Inhaled medication use, with correct inhaler technique, reevaluation visits by a multidisciplinary team, and changes in lifestyle habits are strategic measures in the treatment of asthma in childhood. 4 …”
Section: To the Editormentioning
confidence: 99%
“…Parents’ knowledge about asthma and its triggers is very important, as it may influence treatment adherence and control of symptoms 4 . The degree of awareness of parents and caregivers may be one of the main causes of demands for emergency care and the rate of hospitalization of children due to asthmatic crises, making the disease control more difficult and impairing quality of life (QoL) levels of both children and their relatives 5 …”
Section: Introductionmentioning
confidence: 99%